2016
DOI: 10.1007/s00467-016-3503-5
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation fails to provide adequate growth in children with chronic kidney disease born small for gestational age

Abstract: In children born SGA, growth outcome after KTx is significantly more impaired and affected by different clinical parameters compared with non-SGA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Treatment with recombinant human growth hormone (rhGH) is a measure proven to improve adult height in short children with CKD ( 13 ). The positive results from initial clinical trials have been confirmed by several large, prospective, observational studies and registries, underlining the importance of its use in this population in order to improve growth outcome ( 19 , 37 41 ). Clinical practice recommendations for the use of rhGH in pediatric CKD patients have been provided by expert committees ( 13 , 42 ).…”
Section: Prevention and Treatmentmentioning
confidence: 87%
“…Treatment with recombinant human growth hormone (rhGH) is a measure proven to improve adult height in short children with CKD ( 13 ). The positive results from initial clinical trials have been confirmed by several large, prospective, observational studies and registries, underlining the importance of its use in this population in order to improve growth outcome ( 19 , 37 41 ). Clinical practice recommendations for the use of rhGH in pediatric CKD patients have been provided by expert committees ( 13 , 42 ).…”
Section: Prevention and Treatmentmentioning
confidence: 87%
“…From May 1998 until November 2019, a total of 947 children with CKD stages 3–5D and after KT were enrolled in the CKD Growth and Development Study, which is a prospective, observational cohort study performed at two pediatric nephrology centers in Germany (Hannover Medical School and Charité Universitätsmedizin Berlin). Patients are followed up at yearly intervals for clinical, biochemical and anthropometric assessment as previously described [ 19 ]. The study was approved by the local ethics committees, and research was performed in accordance with the declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Whether the type of transplantation (living versus deceased donor; pre-emptive KT versus prior dialysis) or treatment with recombinant human growth hormone (GH) prior to KT impact on post-transplant growth are largely unknown [ 5 , 10 , 15 ]. Previous analyses mainly coming from patient registries did not include detailed data on factors affecting growth, such as abnormal birth history, low parental height, pubertal status, and medication use (i.e., steroids, GH) and could therefore not adjust for these variables [ 13 , 16 19 ]. Finally, CKD 5 in children is associated with more severe impairment of leg growth in comparison to trunk growth resulting in disproportionate short stature [ 13 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Birth parameters are important determinants of posttransplant growth. Children born small for gestational age (SGA) have significantly poorer growth outcome after KT compared with non-SGA patients, and their growth is more likely to be affected by other factors such as use of rhGH in the pre-transplant period, preemptive KT, and graft function [63].…”
Section: Other Factorsmentioning
confidence: 99%